Internet of Things for Urban Infrastructure: Applications, Challenges, and Future Directions – A Review - Alif Noorachmad Muttaqin; Alaric Rasendriya Aniko; Muhamad Ivan Fadilah; Fauzi Hizbullah; Sahidan Abdulmana (Yayasan Asmin Intelektual Berkah, 2025)
The Internet of Things (IoT) has emerged as a transformative technology in the development of urban infrastructure, enabling real-time data collection, intelligent decision-making, and integrated service delivery. This study explores the implementation of IoT in various urban domains, including transportation management, environmental monitoring, smart parking, structural health surveillance, and smart city integration. The findings highlight significant improvements in operational efficiency, system resilience, and environmental sustainability. However, large-scale adoption still encounters challenges such as cybersecurity risks, interoperability issues, device reliability, and maintenance demands, along with socio-economic barriers including high implementation costs, limited technical expertise, and complex regulatory frameworks. To address these challenges, the study recommends adopting advanced technologies such as edge computing, artificial intelligence, and blockchain, establishing global interoperability standards, and fostering cross-sector collaborations. Furthermore, innovative financing models and inclusive public policies are essential to ensure secure, efficient, and sustainable IoT deployment. The research contributes to a deeper understanding of the role of IoT in shaping future smart cities, providing a framework for policymakers, urban planners, and technology developers.